LEARNING OF VOCATIONAL SKILL FOR EMPOWERMENT THE SPIRIT OF SPECIAL NEEDS OF CHILDREN - Wiratman, Arwan; Yuliana, Ivo; MW, Roihana (JPI (Jurnal Pendidikan Inklusi), 2018)
The child with special needs has barriers on the function of the development Several aspects of emotional, physical and mental or any of aspects. The child with special needs has learning modalities that enable them to make-adaption with Reviews their environments. They need independence to adapt. One of the approaches to establish Reviews their independency is through the learning skills to develop self-help and economic activity. Reviews These are two vital aspect for the independence of the child with special needs.